Timber hollow-box floors: Sound insulation measurement results and analysis. Issue 3 (September 2022) - Homb, Anders; Conta, Simone
We performed measurements of the sound reduction index and impact sound pressure level for a range of lightweight floating floors installed on a hollow-box timber floor. The measurements were performed in the laboratory according to the relevant standards. We tested different configurations, varying the cavity filling of the bare floor and the assembly of the lightweight floating floor. We tested floating floors with a continuous elastic layer with high and low dynamic stiffness, floating floors on elastic load-bearing units and a basic vinyl covering of the bare floor. The results show that a wide range of sound insulation can be achieved, making the hollow-box floor elements suitable for different purposes. Best performance is achieved with elastic load-bearing units installed on the bare floor with gravel in the cavity. Detailed analysis of the achievable sound insulation improvement is also given. This shows that reasonably reliable predictions can be made using well-known equations from the literature. Key parameters are the resonance frequency of the system, determined by the mass per unit area of the bare floor and of the floating floor as well as the dynamic stiffness of the resilient layer, and the configuration of the elastic layer. The results and the highlighted prediction equation offer a solid basis to help develop solutions to meet different sound insulation requirements and make the hollow-box floor elements suitable for urban buildings with several purposes, ranging from office/commercial to educational and residential.